2018
DOI: 10.5530/pj.2018.3.68
|View full text |Cite
|
Sign up to set email alerts
|

Ficus religiosa Tree Leaves as Bioindicators of Heavy Metals in Gorakhpur City, Uttar Pradesh, India

Abstract: Objective: The present work investigates the metal uptake of the plant Ficus religiosa leaves collected from nine experimental sites in Gorakhpur, Uttar Pradesh. Materials and Methods: The concentration of lead in leaves was determined with help of atomic absorption spectrophotometer. Results: The level of the lead in leaves of Ficus religiosa was much higher than the limits recommended by World Health Organization (WHO). The bioaccumulation of lead was highest in site 2 (Gayatri nagar) i.e. 14.1 mg kg-1 dry w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…An excessive amount of this heavy metal may cause serious problems [5]. These heavy metals can be of great concern to biological organisms since they can react with many chemicals essential for biological processes [6]. Plants absorb the Pb through their roots.…”
Section: Introductionmentioning
confidence: 99%
“…An excessive amount of this heavy metal may cause serious problems [5]. These heavy metals can be of great concern to biological organisms since they can react with many chemicals essential for biological processes [6]. Plants absorb the Pb through their roots.…”
Section: Introductionmentioning
confidence: 99%
“…While the background values of Pb content in Platanus orientalis, Robinia pseudoacacia and Ulmus minor leaves amounted 2,700 ppb, it was determined that Pb content increased to 15,700 ppb in areas with heavy traffic and up to 18,800 ppb at Gisha bridge (Abbasi et al 2017). Another study pointed out that the Pb concentration in the leaves of Ficus religiosa increased up to 14,100 ppb, and the correlation analysis pursued by the authors revealed a robust correlation between traffic density and Pb accumulation in plants (Agrahari et al 2018). In many studies it has been confirmed that Pb concentration increases depending on traffic density (Al-Shidi et al 2020, Juwah and Tachere 2021, Soba et al 2021.…”
Section: Discussionmentioning
confidence: 95%
“…Medidas que possam prevenir a liberação de Pb na atmosfera são essenciais, visto que a utilização de automóveis não para de crescer. Uma alternativa é a LRP denominada de gasolina de reposição de Pb, que não contém Pb em sua composição (AGRAHARI et al, 2018). É possível notar que há uma diferença no grau de poluentes atmosféricos entre áreas residenciais e industriais, sendo essa última a que mais apresenta poluentes e efeitos nas plantas.…”
Section: Plantasunclassified